Pengaruh Time Interest Earned dan Earning Per Share Terhadap Harga Saham Perusahaan Rokok yang Listing di BEI - Putri Noviyani (Value : Journal of Management and Business, 2023)
Cigarette companies are companies that belong to the primary purchaser items sector. The share prices of cigarette companies have continued to fall since the outbreak of Cocid-19. The lockdown policy has made cigarette companies experience a decline in performance. The observe targets to decide the impact of TIE and EPS on the share prices. The sample taken is a number of 4 companies acquired thru purposive sampling method. Before testing the hypothesis, the regression model is first tested with classical assumptions so that the data is feasible for testing the hypothesis. with a purpose to make sure that the facts are suitable for testing the hypothesis, the regression model is first tested using conventional assumptions. The analytical tools used are Microsoft Excel and SPSS 25 software. The results found that there is no partial effect of TIE on stock prices. Then there is the partial influence of EPS on stock prices. Simultaneously, TIE and EPS have an effect on stock prices.